2019
DOI: 10.1001/jamapsychiatry.2019.2516
|View full text |Cite|
|
Sign up to set email alerts
|

In Vivo Imaging of Translocator Protein in Long-term Cannabis Users

Abstract: IMPORTANCE Cannabis is the most commonly used illicit drug in the world. Cannabinoids have been shown to modulate immune responses; however, the association of cannabis with neuroimmune function has never been investigated in vivo in the human brain.OBJECTIVE To investigate neuroimmune activation or 18-kDa translocator protein (TSPO) levels in long-term cannabis users, and to evaluate the association of brain TSPO levels with behavioral measures and inflammatory blood biomarkers. DESIGN, SETTING, AND PARTICIPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 64 publications
1
33
3
Order By: Relevance
“…Furthermore, we found no significant difference using an ANCOVA between brain TSPO binding in the small MA smoking (n = 8) and nonsmoking groups (n = 3) and no significant correlation between [F‐18]FEPPA binding and number of cigarettes typically used. A recent study found elevated [F‐18]FEPPA binding in chronic cannabis users 40 ; in our small sampled study, we do not find difference between MA users who used cannabis vs those who did not.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Furthermore, we found no significant difference using an ANCOVA between brain TSPO binding in the small MA smoking (n = 8) and nonsmoking groups (n = 3) and no significant correlation between [F‐18]FEPPA binding and number of cigarettes typically used. A recent study found elevated [F‐18]FEPPA binding in chronic cannabis users 40 ; in our small sampled study, we do not find difference between MA users who used cannabis vs those who did not.…”
Section: Discussioncontrasting
confidence: 95%
“…However, results of a PET study showed no association with cocaine use on brain TSPO binding (using a secondgeneration tracer) in the human. 33 Brody et al 37,38 40 ; in our small sampled study, we do not find difference between MA users who used cannabis vs those who did not.…”
Section: Resultscontrasting
confidence: 52%
“…A second possibility is that the lower FAAH in CU is a compensatory mechanism to account for a downregulation of anandamide in CU. Alternatively, given that THC has been shown to suppress immune responses in cell models, 44 Boileau et al proposed that CU might exhibit lower FAAH alongside a decrease in microglia activity/density; however, findings from our group do not support this postulation 45 …”
Section: Discussioncontrasting
confidence: 81%
“…Time-activity curves were extracted for the cerebellum, dorsolateral prefrontal cortex (DLPFC), and medial prefrontal cortex (MPFC) using a validated in-house imaging pipeline (Rusjan et al, 2006). These ROIs were chosen based on previous literature reporting relevant alterations in TSPO and on their established importance to schizophrenia-spectrum disorders (Da Silva, Hafizi, Rusjan et al, 2019;Da Silva, Hafizi, Watts et al, 2019;Hafizi et al, 2018). All regions of interest were delineated using a proton density MRI in each participant.…”
Section: Image Processing and Calculation Of Total Distribution Volummentioning
confidence: 99%